Cooperative control for multiple autonomous UAV's searching for targets - Flint, M.; Polycarpou, M.; Fernandez-Gaucherand, E. (Proceedings of the 41st IEEE Conference on Decision and Control, 2002, 2002)
The work presented here is in the area of decision and control for autonomous unmanned aerial vehicles (UAVs). Specifically, we formulate the problem of generating near-optimal trajectories to follow in order for several UAVs to cooperatively search for targets in a given area for which some a priori data about target distribution is available. An algorithm that utilizes a model of the cooperation is developed and a dynamic programming implementation is presented as a solution to this problem. Results from simulations are provided to illustrate the usefulness of this approach.